2001
DOI: 10.1093/condor/103.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Fluctuations of Birds, Fruits, and Flowers in a Subtropical Forest of Argentina

Abstract: I quantified monthly variation in species composition and captures of birds in a premontane forest of northwestern Argentina. Seasonal patterns of frugivore-insectivores and nectarivores were compared with fruit and flower abundances, respectively. The composition of the entire bird community fluctuated seasonally; frugivore-insectivores showed a peak in captures during the wet season, insectivores peaked at the end of the dry season, and nectarivores peaked during the dry season. At a local scale (∼50 ha), ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 15 publications
2
47
0
8
Order By: Relevance
“…Breeding Phenology and Clutch Size Sporophila beltoni has a stable and well-defined breeding period (3.8 months), similar to other passerines in subtropical areas of South America (Malizia 2001, Fontana and Repenning 2014 as well as in temperate zones (3.1-4.2 months; Ricklefs 1966, Jones et al 2010. Sporophila beltoni, however, has a shorter breeding period than other congeners (S. collaris and S. hypoxantha, both resident in Formosa, Argentina, a warmer region; S. caerulescens and S. lineola, both migrant, in São Paulo, below 68 latitude) that have breeding periods of 5 months (Francisco 2006, Oliveira et al 2010.…”
Section: Discussionmentioning
confidence: 97%
“…Breeding Phenology and Clutch Size Sporophila beltoni has a stable and well-defined breeding period (3.8 months), similar to other passerines in subtropical areas of South America (Malizia 2001, Fontana and Repenning 2014 as well as in temperate zones (3.1-4.2 months; Ricklefs 1966, Jones et al 2010. Sporophila beltoni, however, has a shorter breeding period than other congeners (S. collaris and S. hypoxantha, both resident in Formosa, Argentina, a warmer region; S. caerulescens and S. lineola, both migrant, in São Paulo, below 68 latitude) that have breeding periods of 5 months (Francisco 2006, Oliveira et al 2010.…”
Section: Discussionmentioning
confidence: 97%
“…Addition of fruit to isolated populations of spiny rats (Proechimys semispinosus) in Panama increased rat reproductive success (Adler 1998). If the strong influence of fruit abundance found in these experimental studies represents a general pattern, then fruit abundance may explain frugivore abundance and behavior in foraging flocks (Chapman et al 1989, Develey andPeres 2000), in individual fruiting trees (Howe and Vande Kerckhove 1980), within and among habitats (Levey 1988, Loiselle and Blake 1993, Malizia 2001, Renton 2001, across regions and elevations (Levey and Stiles 1992, Stouffer and Bierregaard 1993, Rey 1995, Blake and Loiselle 2000, and through time (Martin and Karr 1986, Bronstein and Hoffmann 1987, Kinnaird et al 1996, Wright et al 1999. If the strong influence of fruit abundance found in these experimental studies represents a general pattern, then fruit abundance may explain frugivore abundance and behavior in foraging flocks (Chapman et al 1989, Develey andPeres 2000), in individual fruiting trees (Howe and Vande Kerckhove 1980), within and among habitats (Levey 1988, Loiselle and Blake 1993, Malizia 2001, Renton 2001, across regions and elevations (Levey and Stiles 1992, Stouffer and Bierregaard 1993, Rey 1995, Blake and Loiselle 2000, and through time (Martin and Karr 1986, Bronstein and Hoffmann 1987, Kinnaird et al 1996, Wright et al 1999.…”
Section: Frugivore Responses To Fruit Harvestmentioning
confidence: 95%
“…Studies that have quantified fruit production have generally shown that frugivorous birds (i.e., species that include Ͼ50% fruit in their diet) are most abundant when and where fruits are most abundant (Wheelwright 1983, Levey 1988, Loiselle and Blake 1991, 1993, Jordano 1994, Powell and Bjork 1995, Rey 1995, Kinnaird et al 1996, Malizia 2001, Renton 2001; but see Herrera 1998). A major design constraint of these studies is that they are based on correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Map of the study area above 1200 m altitude (forest-shrubland boundary). Fruit tracking has been documented for obligate as well as partial frugivores (Malizia 2001) and by studying opportunistic frugivores with a broad fruit diet (typical of old world species; Dowsett-Lemaire 1988, Sun andMoermond 1997, Fleming 2005), tracking of overall fruit availability (i.e. Study plots are indicated with white squares (large fragments) and labels (all plots).…”
Section: Study Area and Speciesmentioning
confidence: 99%